2023
DOI: 10.21203/rs.3.rs-2402942/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exceptional multi-year prediction skill of the Kuroshio Extension in a high-resolution decadal prediction system

Abstract: The Kuroshio Extension (KE) has far-reaching influences on climate as well as on local marine ecosystems. Thus, skillful multi-year to decadal prediction of the KE state and understanding sources of skill are both societally important and scientifically challenging. Retrospective forecasts using a high-resolution coupled system at an eddy-rich (0.1°) ocean and 0.25° atmosphere horizontal resolution show exceptional skill in predicting decadal KE variability up to lead year 4, substantially higher than the skil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…While findings from these studies have provided important insights into the potential predictability of WBCs, forecast skill for spatiotemporal variations in frontal‐scale oceanic features in the WBC regions has not been rigorously assessed in an operational sense. Several recent studies have demonstrated operational dynamical forecasting systems that can make skillful muti‐year predictions of large‐scale features of the Kuroshio Extension (KE) (Joh et al., 2022; Kim et al., 2023; Siqueira et al., 2021). However, the horizontal resolutions of ocean models and/or initial conditions adopted in these studies may not be sufficient to explicitly resolve the frontal structure of WBC jets and vigorous mesoscale eddies.…”
Section: Introductionmentioning
confidence: 99%
“…While findings from these studies have provided important insights into the potential predictability of WBCs, forecast skill for spatiotemporal variations in frontal‐scale oceanic features in the WBC regions has not been rigorously assessed in an operational sense. Several recent studies have demonstrated operational dynamical forecasting systems that can make skillful muti‐year predictions of large‐scale features of the Kuroshio Extension (KE) (Joh et al., 2022; Kim et al., 2023; Siqueira et al., 2021). However, the horizontal resolutions of ocean models and/or initial conditions adopted in these studies may not be sufficient to explicitly resolve the frontal structure of WBC jets and vigorous mesoscale eddies.…”
Section: Introductionmentioning
confidence: 99%